Re-thinking the Agricultural Land Destruction and Environmental Impact Assessment in Turkey - Ozugul, Mehmet Doruk (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2010)
By definition and through their practical application, conservation laws, planning and the Environmental Impact Assessment should all be important tools which serve a basic aim, namely the conservation of nature. However, in our country, despite the existence of all three tools, the destruction of the natural environment is a growing problem. In this case, it seems more meaningful to re-examine to what extent all these tools are serving to natural conservation aim. Within this context, this study aims to give satisfactory replies to two major questions. The first question is how functional and successful a tool for protescting the environment the Environmental Impact Assessment actually is in Turkey, given its project-orientated application. Agricultural land is a vital natural asset in this country, and this study makes use of quantative research to provide an accurate answer to this question. The second question considered in the study is, what factors in the process result in major loss of agricultural land? In this study where agricultural land losses of the provinces is the dependent variable, 11 independent variables, including Environmental Impact Assessment decisions, are evaluated to explain the changes in the dependent variable. The study draws two major conclusions. First, that the Environmental Impact Assessment, as it is managed in our country, does not serve a comprehensive protection function. And second, the independent variables which are used in this study put agricultural land losses at a level of 73%.
Keywords: Environmental impact assessment; strategic environmental assessment; sustainability; Architecture